1991
DOI: 10.1007/bf00845111
|View full text |Cite
|
Sign up to set email alerts
|

Self-efficacy, reasoned action, and oral health behavior reports: A social cognitive approach to compliance

Abstract: The usefulness of a social cognitive approach to compliance with brushing and flossing behavior recommendations was tested with 39 patients recruited from the State University of New York at Buffalo Periodontal Disease Clinical Research Center. Participants completed mailed study instruments assessing Fishbein and Ajzen's theory of reasoned action variables, Bandura's self-efficacy variables, and frequency of brushing and flossing behavior. Results indicated positive attitudes, beliefs, and norms for brushing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
91
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(98 citation statements)
references
References 16 publications
5
91
2
Order By: Relevance
“…In the dental field, the relationship between self-efficacy and oral hygiene behaviour, such as toothbrushing or flossing, has been examined in several studies (McCaul et al, 1985;Tedesco et al, 1991Tedesco et al, , 1992Stewart et al, 1997;Syrjälä et al, 1999Syrjälä et al, , 2004. McCaul et al (1985) analysed self-efficacy among college students with respect to brushing and flossing to predict task-related behaviours, and found that the retrospectively self-reported and prospective frequency of the two examined oral care factors were significantly associated with self-efficacy.…”
Section: Self-efficacy In the Clinical Practicementioning
confidence: 99%
See 2 more Smart Citations
“…In the dental field, the relationship between self-efficacy and oral hygiene behaviour, such as toothbrushing or flossing, has been examined in several studies (McCaul et al, 1985;Tedesco et al, 1991Tedesco et al, , 1992Stewart et al, 1997;Syrjälä et al, 1999Syrjälä et al, , 2004. McCaul et al (1985) analysed self-efficacy among college students with respect to brushing and flossing to predict task-related behaviours, and found that the retrospectively self-reported and prospective frequency of the two examined oral care factors were significantly associated with self-efficacy.…”
Section: Self-efficacy In the Clinical Practicementioning
confidence: 99%
“…McCaul et al (1985) analysed self-efficacy among college students with respect to brushing and flossing to predict task-related behaviours, and found that the retrospectively self-reported and prospective frequency of the two examined oral care factors were significantly associated with self-efficacy. Subsequently, Tedesco et al (1991) reported that the addition of selfefficacy variables to the theory of reasoned action variables markedly increased the observed variance in brushing and flossing behaviours. Furthermore, it was demonstrated that cognitive behavioural intervention resulted in a delayed relapse in protective oral selfcare behaviour and improved self-efficacy towards flossing (Tedesco et al, 1991).…”
Section: Self-efficacy In the Clinical Practicementioning
confidence: 99%
See 1 more Smart Citation
“…This process however, is dependent on behavioural changes and changes in relation to thoughts and beliefs regarding oral health (Tedesco, et al, 1991). Patient compliance is necessary for the successful outcome of preventive or treatment recommendations (Blinkhorn, Non-compliance with oral self-care recommendations is the key problem in the prevention of poor oral health (Widström, 2004).…”
Section: Oral Health Behavioural Changementioning
confidence: 99%
“…According to dental studies, self-efficacy have been found to relate to tooth brushing and flossing (McCaul et al 1985, Tedesco et al 1991. Self-efficacy concerning tooth brushing and flossing have been found to associate with the frequencies of tooth brushing, flossing and dental visiting (Stewart et al 1997), but self-efficacy has not been found to associate with the oral hygiene status (Wolfe et al 1991).…”
Section: Self-efficacymentioning
confidence: 99%